Penentuan Parameter Nonspesifik Ekstrak Etanol Kulit Batang Tandui (Mangifera rufocostata Kosterm.) - Indah Widya Lestari; Revita Saputri; Rahmi Muthia; Eka Fitri Susiani (Universitas Borneo Lestari, 2023)
The cortex of tandui has the potential to be a folk remedy. As an ingredient in traditional medicine, it is necessary to characterize the cortex of tandui as a first step in knowing the quality of the quality of the extract in accordance with the established extract monograph, namely with nonspecific parameters. This study aims to determine the results of the characterization value of nonspecific parameters of ethanol extract of cortex tandui (Mangifera rufocostata Kosterm.). In this study, the extraction of the cortex tandui used the maceration method with a 70% ethanol solvent with a yield gain of 21.1%. The determination of nonspecific parameters includes type weight, moisture content, ash content, acid insoluble ash content, heavy metal contamination, yeast mold contamination and microbial contamination. Ethanol extract of the cortex tandui (Mangifera rufocostata Kosterm.) has successive nonspecific parameter characterization values, namely, type weight of 1.11 grams, moisture content of 42.73%, ash content of 2.28%, acid insoluble ash content of 0.035%, lead metal contamination (Pb) <0.001 mg/kg, cadmium metal contamination (Cd) < 0.001 mg/kg, yeast mold contamination 1,2 × colonies/g and microbial contamination < 1,0 × colonies/g. From the above results, it can be implied that the determination of nonspecific parameters of the ethanol extract of the cortex tandui (Mangifera rufocostata Kosterm.) meets the requirements set except for the parameters of moisture content that exceeds the requirements.